Intervention of the Rehabilitation Nurse in Women with Urinary Incontinence after stroke - Braga, Marta (2023)
Introduction: Urinary incontinence has a high prevalence in patients with stroke. Conservative treatment is the most recommended, as it involves lower financial costs and side effects. This study aims to: Evaluate the effect of a Rehabilitation Program in the Management of Urinary Incontinence in women after the occurrence of a stroke. Methodology: This is a Multiple Case Study, with a quantitative method. The sample consisted of (n=5) women aged between 53 and 87 years. A rehabilitation program was applied from the detection of urinary incontinence to the time of discharge. The instruments used were: Broome Self-Efficacy Scale and Voiding Diary. Results: This study allowed us to conclude that the users who initially had urgency and loss of urine, no longer did. In the scores of the Broome self-efficacy scale: in the 1st assessment, in part A and B all had low self-efficacy, except for Case 8 which in part B had moderate self-efficacy. In the 2nd evaluation, all had high self-efficacy. Discussion: When comparing before and after the program, all had positive results in relation to urinary urgency, urine leakage, in the level of confidence in performing pelvic muscle contractions, without urine leakage. Conclusion: The rehabilitation program for the management of urinary incontinence had a positive effect on all study users.